Biotransformation of Agricultural Waste and by-Products 2016
DOI: 10.1016/b978-0-12-803622-8.00009-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of Dicarboxylic Acid Platform Chemicals Using Yeasts

Abstract: The biotechnological production of biobased dicarboxylic acids has recently become a hot topic in industrial biotechnology, with many investments involved in the development, piloting, and validation at demonstration scale of diverse processes using renewable raw materials. This chapter will review the main markets and applications of commercially relevant dicarboxylic acids and will briefly present their current chemical and biotechnological production processes. The chapter will mainly focus on the particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…HPLC analysis emphasized a reverse contribution of succinic and acetic acid, which is in agreement with the reported effects on the fermentation yields for S. cerevisiae [ 81 , 84 , 85 ]. Acetic acid, a relevant end-product of fermentation, represents a key signature in the volatile acidity of wines and, therefore, in its aroma profile.…”
Section: Resultssupporting
confidence: 87%
“…HPLC analysis emphasized a reverse contribution of succinic and acetic acid, which is in agreement with the reported effects on the fermentation yields for S. cerevisiae [ 81 , 84 , 85 ]. Acetic acid, a relevant end-product of fermentation, represents a key signature in the volatile acidity of wines and, therefore, in its aroma profile.…”
Section: Resultssupporting
confidence: 87%
“…In fact, the acids at pH values higher than their pKa are produced in their dissociated form and have to be converted into their acidic form by adding a strong acid. This results in by-product formation in terms of a salt, which is not desirable in large-scale production processes, and low pH processes are, therefore, considered to be more attractive [ 47 ]. Adaptive evolution, a genome-wide engineering approach, has become a commonly performed strategy for improvement of the tolerance to industrially relevant stresses [ 63 ], single inhibiting compounds present in lignocellulosic hydrolysates [ 64 ] or even complex mixtures of inhibitors and feedstocks as such [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under acidic conditions, the dicarboxylic acids occur in un-dissociated forms, which potentially reduces their recovery and downstream processing costs. Successful metabolic engineering strategies leading to relevant yields of dicarboxylic acids mainly from glucose in yeast have been applied [ 45 , 46 ], with succinic acid being produced by an engineered yeast strain at industrial scale [ 47 ]. Recently, a study demonstrating production of l -malic acid from xylose in a laboratory fed-batch process has been reported [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the promising exploitation studies reported in the literature in recent years, bacteria are very sensitive to low pH and the presence of sulphur dioxide in the media, do not display post-translational modifications, have a small size and a low density, and are associated with a larger set of pathogenic strains [ 42 ]. In contrast to prokaryotes, yeast-based strategies are economically superior because yeasts are highly tolerant to lower pH environments, are larger in size, allow post-transcriptional modifications of proteins (i.e., glycosylation), have increasing genetic mutant libraries and omics repertoires, and have effective adapting abilities to stress conditions and are generally recognized as safe (GRAS) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ], reinforcing their potential as an asset model for the most diverse fields. Through ALE strategies, S. cerevisiae strains were successfully evolved, considering a panoply of biotechnological important traits: (i) Huang and Kao [ 50 ] and Randez-Gil et al [ 51 ] successfully evolved S. cerevisiae strains into higher thermotolerant strains that were able to grow and develop at 40 and 42 °C, respectively; (ii) Cadière et al [ 52 ] increased the carbon flux through the pentose phosphate pathway, increasing fermentation rates and different volatile aromas; (iii) Pereira et al [ 53 ] exploited tolerance mechanisms with heightened acid tolerance by the S. cerevisiae strains understudy; (iv) De Vero et al [ 54 ] obtained a reduction of sulphites (<10 mg −1 ) and H 2 S production levels; (v) Novo et al [ 55 ] enhanced CO 2 production, obtaining inferior sugar amounts at the end of fermentation, while also allowing faster fermentation kinetics, etc.…”
Section: Evolution Of Non-conventional Yeast Species Through Alementioning
confidence: 99%